2003
DOI: 10.1126/science.1088477
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of MEF2A in an Inherited Disorder with Features of Coronary Artery Disease

Abstract: The early genetic pathway(s) triggering the pathogenesis of coronary artery disease (CAD) and myocardial infarction (MI) remain largely unknown. Here, we describe an autosomal dominant form of CAD/MI (adCAD1) that is caused by the deletion of seven amino acids in transcription factor MEF2A. The deletion disrupts nuclear localization of MEF2A, reduces MEF2A-mediated transcription activation, and abolishes synergistic activation by MEF2A and by the transcription factor GATA-1 through a dominant-negative mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
275
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(282 citation statements)
references
References 18 publications
(23 reference statements)
2
275
2
3
Order By: Relevance
“…Indeed, ablation of MEF2 in the heart can lead to dilated cardiomyopathy in mice and has been linked to increased risk of myocardial infarction in humans (46,47). These phenotypes may be related to the ability of MEF2 to regulate expression of the PPARγ coactivator-1α (PGC-1) transcription factor, a master regulator of mitochondrial biogenesis (48).…”
Section: Figurementioning
confidence: 99%
“…Indeed, ablation of MEF2 in the heart can lead to dilated cardiomyopathy in mice and has been linked to increased risk of myocardial infarction in humans (46,47). These phenotypes may be related to the ability of MEF2 to regulate expression of the PPARγ coactivator-1α (PGC-1) transcription factor, a master regulator of mitochondrial biogenesis (48).…”
Section: Figurementioning
confidence: 99%
“…Case-control association studies have identified several proinflammatory genes with variants that are associated with either an increased risk of myocardial infarction or a protective effect [7][8][9] . Four genome-wide scans in families with myocardial infarction have yielded several loci with formidable linkage peaks, but the gene(s) underlying these loci have not yet been identified [10][11][12][13][14] . In addition, one large pedigree study identified a deletion mutation of a transcription factor gene, MEF2A, with autosomal dominant transmission 14 .…”
mentioning
confidence: 99%
“…Four genome-wide scans in families with myocardial infarction have yielded several loci with formidable linkage peaks, but the gene(s) underlying these loci have not yet been identified [10][11][12][13][14] . In addition, one large pedigree study identified a deletion mutation of a transcription factor gene, MEF2A, with autosomal dominant transmission 14 . This is an interesting cause of myocardial infarction, but the prevalence of this or other mutations in MEF2A outside this family remains to be determined.…”
mentioning
confidence: 99%
“…One study by Wang et al examined a family cohort with a high prevalence of myocardial infarction and found linkage for a region on chromosome 15. [8] The putative candidate gene in this chromosomal region was identified as myocyte enhancer factor 2A (mef2a). In another linkage study, Broeckel et al studied a group of 513 unrelated families in which there was at least one member with a documented myocardial infarction.…”
Section: Linkage Analysismentioning
confidence: 99%